How do natural hazards affect participation in voluntary association? The social impacts of disasters in Japanese society. (March 2019) - Lee, Juheon; Fraser, Timothy
Abstract: This study focused on the way individuals' past experiences with disasters and their perceived risks of disasters affect their involvement in voluntary associations, which are important indicators of social capital. Moreover, as recent social capital studies have examined the different types of associations that contribute to the formation of social capital in various ways, for this present study, associations were categorized as civic, reward-based, and social/recreational. The results indicate that both respondents' experiences with disasters and their perceived risks of disasters tend to increase both the number of associations in which they participate and their degree of involvement. However, experiences related to disasters had a higher impact on the number of associations in which residents participate than on their degree of involvement. Individuals' experiences with disasters also increased their tendency to join civic associations, whereas their perceived risks of disasters increased participation in both civic and reward-based associations. Social/recreational associations were not significantly affected by either disaster experiences or the perceived risks of a disaster.